Find f(1); f(2); f(3); f(4) and f(5) if f(n) is defined recursively by f(0) = 3 and for n = 0; 1; 2 for: f(n+1)= 3^(f(n)/3)
Follow Math Help Forum on Facebook and Google+
Originally Posted by orendacl Find f(1); f(2); f(3); f(4) and f(5) if f(n) is defined recursively by f(0) = 3 and for n = 0; 1; 2 for: f(n+1)= 3^(f(n)/3) Let n=0, then $\displaystyle f(0+1)=f(1)=3^{f(0)/3}=3^{3/3}=3^1=3$ Continue by letting n=1,2,3,4
Originally Posted by orendacl Find f(1); f(2); f(3); f(4) and f(5) if f(n) is defined recursively by f(0) = 3 and for n = 0; 1; 2 for: f(n+1)= 3^(f(n)/3) $\displaystyle f(1) = 3^{\frac{f(0)}{3}} = 3^{\frac{3}{3}} = ??$ $\displaystyle f(2) = 3^{\frac{f(1)}{3}} = ??$ etc. EDIT: too slow again
Last edited by pomp; Jul 19th 2009 at 10:37 AM.
View Tag Cloud